Whistleblowing Need not Occur if Internal Voices Are Heard: From Deaf Effect to Hearer Courage; Comment on "Cultures of Silence and Cultures of Voice: The Role of Whistleblowing in Healthcare Organisations" - Sonja R. Cleary; Kerrie E. Doyle (Kerman University of Medical Sciences, 2016)
Whistleblowing by health professionals is an infrequent and extraordinary event and need not occur if internal voices are heard. Mannion and Davies' editorial on "Cultures of Silence and Cultures of Voice: The Role of Whistleblowing in Healthcare Organisations" asks the question whether whistleblowing ameliorates or exacerbates the 'deaf effect' prevalent in healthcare organisations. This commentary argues that the focus should remain on internal processes and hearer courage.